2020
DOI: 10.3390/app10061950
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Water Infiltration and Soil Water Repellency in Brazilian Atlantic Forest Soils

Abstract: This study presents the results of the soil hydraulic characterization performed under three land covers, namely pasture, 9-year-old restored forest, and remnant forest, in the Brazilian Atlantic Forest. Two types of infiltration tests were performed, namely tension (Mini-Disk Infiltrometer, MDI) and ponding (Beerkan) tests. MDI and Beerkan tests provided complementary information, highlighting a clear increase of the hydraulic conductivity, especially at the remnant forest plots, when moving from near-saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
(102 reference statements)
1
13
0
Order By: Relevance
“…The WDPT allowed to detect a stronger water repellency at the NR and RF sites. Our findings are in agreement with previous studies in tropical ecosystems [61][62][63], which have reported hydrophobicity under forest cover. It is important to highlight that soil water repellency can negatively affect the soil infiltration process and increase soil erosion [48].…”
Section: Discussionsupporting
confidence: 94%
“…The WDPT allowed to detect a stronger water repellency at the NR and RF sites. Our findings are in agreement with previous studies in tropical ecosystems [61][62][63], which have reported hydrophobicity under forest cover. It is important to highlight that soil water repellency can negatively affect the soil infiltration process and increase soil erosion [48].…”
Section: Discussionsupporting
confidence: 94%
“…The MDI infiltrometer is commonly used for field measurements, given its small size and easy handling (Robichaud, Lewis, & Ashmun, 2008). The MDI test is an effective indirect technique to quickly assess the existence and degree of water repellency of soil, since sorptivity and early infiltration rates are good indicators of repellency (Lozano‐Baez et al, 2020; Robichaud, Pierson, et al, 2008; Williams et al, 2020). However, we preferred to rely on direct measurements of SWR, using the WDPT method, which is a simple but reliable procedure to measure SWR (Dekker, Ritsema, Oostindie, Moore, & Wesseling, 2009; Doerr, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…This SI collects 12 original contributions focused on soil use and management, soil conservation, as well as on the impact of some pollutants on the soil. Specifically, the SI collects nine research papers [10][11][12][13][14][15][16][17][18], two reviews [19,20] and one methodological work [21]. Eight of the twelve manuscripts considered the effects of soil use and management (topic I) [10][11][12][13][14][15][16]21], while the remaining four [17][18][19][20] evaluated the impact of some soil contaminants (e.g., crude oil, tungsten, copper and polycyclic aromatic hydrocarbons) (topic II).…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…Regarding the aforementioned nine investigations (i.e., research papers), seven were carried out in the field [10][11][12][13][14][15][16], while the others accounted for pot [17] or microcosm [18] experiments. From a geographical point of view, five "field open-air" investigations were carried out in Italy (three in the south [12,13,16], one in the center [15] and one in the north [10] of Italy), while the remaining investigations were in Brazil [14] and China [11].…”
Section: Overview Of This Special Issuementioning
confidence: 99%
See 1 more Smart Citation